Low-temperature Catalytic Oxidation of White Spirit Vapor in Air by Binary Oxides of FeO-MnOx Supported on OMS-2 Material - Ngo Quoc Nguyen; Pham Duy Quang; Nguyen Ha Nhu; Le Thi Van Anh; Nguyen Thi Thuy; Vo Thanh Hang; Le Van Thang; Nguyen Thi Le Lien; Nguyen Trung Thanh; Nguyen Nhat Huy (Applied Environmental Research)
In this work, catalysts of iron and manganese oxides supported on OMS-2 were prepared and applied to remove white spirit (WS) in air. Among the fabricated catalysts, the FeO-MnOx/OMS-2 catalyst with a surface Fe+Mn loading of 15% (Fe:Mn = 6:4) exhibited the highest catalytic performance, achieving a high WS removal efficiency of 97.91% at 200 °C. The catalyst retained the cryptomelane-type tunnel structure of OMS-2 and possessed enhanced redox activity due to the synergistic interaction between surface Fe and Mn species. The physico-chemical properties were characterized via BET, EDS, FTIR, XRD, and SEM. The suitable conditions for WS oxidation were identified as 1 g of catalyst, a 1 L min-1 gas flow rate, and a maximum inlet concentration of 2000 ppm at a low operating temperature of 200 °C. While the catalyst proved highly effective in WS treatment, durability tests indicated performance degradation over prolonged use, highlighting a direction for future enhancement.